THE STUDENTâ€™S METACOGNITIVE SKILLS OF PROSPECTIVE PRIMARY SCHOOL TEACHERS - Maryani, Ika; Alhakim, Muhamad Arif; Gestiardi, Rivan (International Journal of Educational Management and Innovation, 2021)
Metacognitive skill is essential to have by every individual, including the prospective teachers' students. Some teachers who have not trained in metacognitive ability would be caused by the lack of understanding of the stages in carrying out metacognitive ability. It has not realised that metacognitive ability can affect students' learning process and learning outcome. The students who have the excellent metacognitive ability can develop metacognitive domain-oriented learning. This study aims to know the metacognitive skills of prospective primary school teachers in Universitas Ahmad Dahlan. This research used a quantitative approach to descriptive type and survey method. The samples are 100 students of elementary school educations of Universitas Ahmad Dahlan consisted of the semester II, IV, and VI. The instrument used Metacognitive Ability Inventory (MAI) with the Likert scale(1-5). Data were analysed using descriptive statistics to determine the Mean, standard deviation, percentage, and metacognitive categorisation of elementary school education students.Â The research result showed a low-medium range category. It influenced by some factors related to the inadequate metacognitive development of prospective primary school teachers. Judging from the cognitive knowledge aspect, the high category of the percentage calculation of cognitive knowledge aspects is in the declarative knowledge aspect. In the cognitive regulation aspect, planning becomes the highest percentage of cognitive regulation aspect.